Native Family Law, Indian Child Welfare Act and Tribal Sovereignty - Akhtar, Zia (First Peoples Child & Family Review, 2013)
There has been historical abuse of Native American children in the U.S. which began in the late 19th century in what is known as the residential school movement. It led to their forced integration on pain of removing and eradicating traces of their Indian heritage. The lack of protection for Indigenous children in being transferred from the reservations to non- Indian foster parents caused the U.S. Congress to use their legislative power and enact the Indian Child Welfare Act of 1978 [ICWA]. This has intervened in a process that is aimed at keeping Native American children within the tribe of their parents over the last 35 years. The result of the ICWA is that it has led to the greater supervision by tribal courts over children but it has caused a conflict to arise with the state courts due to jurisdictional reasons that allows guardianship and supervision to non-Indian parents. The Arizona Court of Appeals has recently ruled in Navajo Nation v. Arizona Department of Economic Security (2012) CA-JV 11-0123 that an Indian child can stay with his non-Native foster parents despite the protests of the tribe that it was infringing the provisions of the statute. This article is intended for the practitioner and policy makers and brings to the fore the issues of the preservation of children on reservation lands, and the need for a greater care consideration in the determination if they should be transferred to foster parents outside the tribe’s jurisdiction. It also conducts a comparison with Canada where First Nations children have also suffered abuse and where there is an ongoing debate about the course of action to prevent the appropriation of children from the reserves to live with the non-Native foster parents.